Effects of Acremonium cellulase and heat-resistant lactic acid bacteria on lignocellulose degradation, fermentation quality, and microbial community structure of hybrid elephant grass silage in humid and hot areas - Chen, Chen; Xin, Yafen; Li, Xiaomei; Ni, Haoran; Zeng, Tairu; Du, Zhaochang; Guan, Hao; Wu, Yushan; Yang, Wenyu; Cai, Yimin; Yan, Yanhong (Frontiers in Microbiology, 2022)
In order to better evaluate the effects of Acremonium cellulase (AC) and previously screened heat-resistant Lactobacillus plantarum 149 (LP149) on lignocellulose degradation, fermentation quality and microbial community during ensiling in humid and hot areas, this study used a small-scale fermentation system to prepare hybrid elephant grass silage at 30°C and 45°C, respectively. Compared to control and commercial inoculant Lactobacillus plantarum (LP), addition of AC or strain LP149 decreased the contents of neutral detergent fiber, acid detergent fiber and cellulose while increased the contents of glucose, fructose and sucrose during fermentation. Furthermore, AC and LP149 treatments altered the microbial communities structure during ensiling. AC treatment provided more substrate for microbial fermentation, resulting in an increase of bacterial alpha diversity. LP149 treatment increased the Lactobacillus abundance and optimized the bacterial community compositions. In addition, AC and LP149 treatments had higher (P < 0.05) lactic acid and acetic acid contents and lower (P < 0.05) pH, butyric acid and NH3-N levels compared to the control. These results indicated that AC and strain LP149 are promising silage additives that can promote lignocellulose degradation and improve fermentation quality of hybrid elephant grass in humid and hot areas.